Changing environment, just transition and job creation perspectives from the south - Kenfack, Chrislain Eric (CLACSO, 2018)
The world in which we currently live is characterised by a multiplicity of challenges that we must face with urgency if we want to avoid future catastrophes. Those challenges, because of the globalisation of systems, have also become global challenges, and need global responses. One of the most important of those challenges faced by the current global community remains the environmental crisis, and more specifically the climate crisis also known as global warming. Most scientists, non-sovereign actors and policy makers are convinced that the salvation of our world definitely depends on urgent and strong actions aimed at reducing the emission of Greenhouse gases and therefore limiting climate change (Mitigation). Moreover, such actions should put in place mechanisms and policies aimed at reducing the impacts of the already occurred climate change on environmental, human and socio-political systems (Adaptation). Beyond this challenge of global concern, there is also the global challenge of unemployment enhanced by the financial and economic crisis as well as the lack of alternative employment policies in a changing environment. These two challenges are important threats not only to the world security, but above all to the sustainable development in general and development in the global South in particular.